Development and evaluation of a novel pre‐operative surgery school and behavioural change intervention for patients undergoing elective major surgery: Fit‐4‐Surgery School. (3rd February 2021) - Fecher‐Jones, I.; Grimmett, C.; Edwards, M. R.; Knight, J. S.; Smith, J.; Leach, H.; Moyses, H.; Jack, S.; Grocott, M. P. W.; Levett, D. Z. H.
Summary: Group pre‐operative education has usually been limited to conditioning expectations and providing education. Prehabilitation has highlighted modifiable lifestyle factors that are amenable to change and may improve clinical outcomes. We instituted a pre‐operative 'Fit‐4‐Surgery School' for patients scheduled for major surgery, to educate and promote healthy behaviour. We evaluated patients' views having attended the school, and after surgery we asked how it had changed their behaviour with a lifestyle questionnaire. The school was launched in May 2016 and was attended by 586/1017 (58%) of invited patients. Patients who did not attend: lived further away, median (IQR [range]) 8 (4–19 [0–123]) miles vs. 5 (3–14 [0–172]) miles, p < 0.001; and were more deprived, Index of Multiple Deprivation Rank decile median (IQR [range]), 6 (4–8 [1–10]) vs. 7 (4–9 [1–10]), p = 0.04. Of the 492/586 (84%) participants who completed an evaluation questionnaire, 462 (94%) would recommend the school to a friend having surgery and 296 (60%) planned lifestyle changes. After surgery, 232/586 (40%) completed a behavioural change questionnaire, 106 (46%) of whom reported changing at least one lifestyle factor, most commonly by increasing exercise. The pre‐operative school was acceptable to patients.